Communication works - Gamble, Teri Kwal; Gamble, Michael , 1943- (McGraw-Hill, 2013)
Presents a practical approach to communication, with a focus on the ways in which diversity, technology, social media, and ethical concerns both enrich and complicate our world. In this title, students learn what role communication plays in their lives today, in the classroom, and tomorrow, in the working world